2013
DOI: 10.1371/journal.pone.0084898
|View full text |Cite
|
Sign up to set email alerts
|

Low Pressure Radio-Frequency Oxygen Plasma Induced Oxidation of Titanium – Surface Characteristics and Biological Effects

Abstract: ObjectiveThis research was designed to investigate the effects of low pressure radio-frequency (RF) oxygen plasma treatment (OPT) on the surface of commercially pure titanium (CP-Ti) and Ti6Al4V. Surface topography, elemental composition, water contact angle, cell viability, and cell morphology were surveyed to evaluate the biocompatibility of titanium samples with different lengths of OP treating time.Materials and MethodsCP-Ti and Ti6Al4V discs were both classified into 4 groups: untreated, treated with OP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…that the level of energy stabilizes after the initial energy bombardment that occurs during the first 5 minutes of application. 21,26 Most plasma studies have evaluated surface changes using atomic force microscope and profilometer 21,22 ; however, considering that these studies reported changes of less than 1 nm, this study evaluated water contact angle instead.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…that the level of energy stabilizes after the initial energy bombardment that occurs during the first 5 minutes of application. 21,26 Most plasma studies have evaluated surface changes using atomic force microscope and profilometer 21,22 ; however, considering that these studies reported changes of less than 1 nm, this study evaluated water contact angle instead.…”
Section: Discussionmentioning
confidence: 99%
“…37 Oxygen plasma treatment can be performed under different atmospheric pressure conditions and with various types of electrically neutral ionized gas as well as using homogenous dielectric barrier discharge, and it has a wide range of applications from industry to medicine. 25,38 Studies examining the effects of oxygen plasma treatment application to titanium material on cell movement and osseointegration 21,22 have reported increases in surface concentrations of reactive species (O 2 ) and hydrophilicity that optimized cell growth. However, few studies 25,33 have looked at the effects of oxygen plasma treatment on bonding ability between titanium surfaces and luting cements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For polymers, plasma bombards the polymer surface, increasing roughness [ 26 , 27 ]. Some relative studies proposed that plasma treatment might cause significant roughness changes on material surfaces, such as polished titanium, chitosan, or poly(etheretherketone) [ 4 , 28 , 29 ]. However, the plasma-treated SLA surface maintained its original surface texture, which contained micro- and sub-micro-scale roughness in all groups (as shown in Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, hydrophilic surfaces exhibit better cell affinity, especially cell adhesion improvement [ 31 ]. A hydrophilic surface modification of titanium influenced differentiation and growth factor production for osteoblast-like cells [ 28 , 32 ]. Buser et al examined the commonly used hydrophilic SLActive implant, which promoted more bone healing in the early stage than the traditional SLA method [ 23 ].…”
Section: Discussionmentioning
confidence: 99%